Body composition and ankle-brachial index in Ghanaians with asymptomatic peripheral arterial disease in a tertiary hospital. Issue 1 (December 2016) - Yeboah, Kwame; Puplampu, Peter; Yorke, Ernest; Antwi, Daniel; Gyan, Ben; Amoah, Albert
Abstract Background Ankle-brachial index (ABI) and indices of obesity are both use to indicate cardiovascular risk. However, association between body composition indices and ABI, a measure of peripheral arterial disease, is inconsistent in various study reports. In this study, we investigated the relationship between ABI and general and central indices of obesity in Ghanaians without history of cardiovascular diseases. Method In a case–control design, ABI was measured in a total of 623 subjects and categorised into PAD (ABI ≤ 0.9, n  = 261) and non-PAD (ABI > 0.9, n  = 362) groups. Anthropometric indices, BMI, waist circumference (WC), waist-hip ratio (WHR) and waist-height ratio (WHtR) were also measured. Results PAD subjects had higher mean BMI (29.8 ± 8.7 vs. 26.5 ± 7.6 kg/m2, p  = 0.043) and waist circumference (95 ± 15 vs. 92 ± 24 cm, p  = 0.034) than non-PAD subjects. In multivariable logistic regression models, having BMI ≥ 30 kg/m2 increased the odds of both unilateral [OR (95 % CI): 2 (1.14–3.51), p  < 0.01] and overall PAD [2 (1.22–3.27), p  < 0.01]. Conclusion In indigenous Ghanaians in our study, PAD participants had higher BMI and waist circumference than non-PAD participants. Also, halving BMI ≥ 30 kg/m2  was associated with twofold increase in the odds of PAD.